Granica południowa Górnego Śląska w ekspertyzach Ministerstwa Spraw Zagranicznych 1945–1947 - Pałys, Piotr (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The article provides an analysis of argumentation substantiating Polish rights to the area of Racibórz and Głubczyce from the years 1945–1947. These arguments were serving primarily to refute Czechoslovakian claims to this region
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne